Demystifying the Out-of-Body Experience: A Practical Manual for Exploration and Personal Evolution by Luis Minero - Sassoli De Bianchi, Massimiliano (Journal of Scientific Exploration, 2013)
I was ver y pleased to learn that Luis Minero had written a book on the out-of-body experience (OBE). I bought it sight unseen, and I was not disappointed. It was back in 2002 that I first came across the author's name in a correspondence to the Journal of Conscientiology (Minero 2002a), the peer-reviewed journal of the International Academy of Consciousness (IAC). In that letter, Minero analyzed with great accuracy, clarity, and thoroughness, the so-called "mind-split" hypothesis, proposed by author Robert Bruce to explain some of the puzzling factors of the OBE phenomenon, such as memory loss and dual consciousness (Bruce 1999). I still remember how impressed I was when I read Minero's step-by-step refutation of Bruce's hypothesis, not only for the care and lucidity of his analysis, but also for his natural, didactical style and the balance with which he was able to strongly criticize weak points of some of the ideas presented, and at the same time give full credit to other innovative aspects of Bruce's work. I rediscovered these same intellectual qualities in other writings of Minero, such as his suggestive essay on lucidocracy (Minero 2002b), a political proposal contemplating the possibility of a government system based on lucidity, with the main goal of facilitating the fulfillment of one's potential or life mission (existential program). I would start by saying that the book's title may possibly seduce the hasty reader in error. Indeed, the demystification in question is not the usual one, consisting in reducing the entire OBE complex of phenomena to a mere hallucination produced by the subject's physical brain, when his or her sensory inputs are altered in some way. Minero, quite to the contrary, considers OBEs as experiences describing real projections of the human consciousness through objective subtle bodies (vehicles of manifestations), which can exist independently of the physical body. The book's demystification is, therefore, of a very different kind: It is about those more mystic-like and folkloristic aspects that have been historically associated with the OBE phenomenon, mostly based on immature, emotional, or superstitious thinking, and which have little to do with a more mature understanding of this fundamental topic.